2018
DOI: 10.1186/s41241-018-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Language as a barrier to cancer clinical trial accrual: assessing consenting team knowledge and practices for cancer clinical trial consent among low English fluency patients

Abstract: Background: Low English fluency in large culturally diverse institutions may contribute to meager minority accrual. Our objective was to: 1) Assess knowledge of proper consenting procedures among the research team when consenting a low English fluency patient. 2) Assess the enrollment rate of participants in cancer therapeutic trials who identify a preferred language other than English. Methods: An anonymous web-based survey was distributed at a single institution to investigators, research staff and translato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
4
18
1
Order By: Relevance
“…OPs, particularly in regional cancer centres, regretted that the protocol excluded non-English-speaking patients and indicated that for those who spoke English as their second language (ESL), many could not read English written materials. This is consistent with past research highlighting low English uency levels in patients as a barrier to recruitment and warranting institutions to explore more effective training opportunities for research staff to engage interpreters and adopt recruitment and study materials in multiple languages (35). Additionally, their feedback changed some of our inclusion/exclusion criteria and broadened the timing of recruitment, training for recruitment plans, and recruitment personnel to work within these varying structures.…”
Section: Discussionsupporting
confidence: 81%
“…OPs, particularly in regional cancer centres, regretted that the protocol excluded non-English-speaking patients and indicated that for those who spoke English as their second language (ESL), many could not read English written materials. This is consistent with past research highlighting low English uency levels in patients as a barrier to recruitment and warranting institutions to explore more effective training opportunities for research staff to engage interpreters and adopt recruitment and study materials in multiple languages (35). Additionally, their feedback changed some of our inclusion/exclusion criteria and broadened the timing of recruitment, training for recruitment plans, and recruitment personnel to work within these varying structures.…”
Section: Discussionsupporting
confidence: 81%
“…None of the trials assessed had a strict language requirement. However, we know that those who do not speak the language of the majority are often indirectly excluded from trials as there are barriers to reading and understanding medical information, even when this is translated [34,35]. The translation of medical literature into a readable format for patients can be difficult, particularly when done by a commercial company [36].…”
Section: Discussionmentioning
confidence: 99%
“…English speakers comprised 92% ( n = 1,421) of the trial participants. For the remaining 8% of the participants, their first language was not English (Staples et al., 2018). However, if there is a plain language document summarising key information about clinical trial participation, physicians may be more willing to provide the plain language document about trial participation to non‐English speaking patients and to consider them as potentially eligible for inclusion.…”
Section: Discussionmentioning
confidence: 99%